Pengenalan Sejarah dan Budaya Lokal Desa Ngegedhawe melalui Produksi Film Dokumenter - Ghedy Frando Kotta; Riang, P. Yoseph; Medho, Yohana Fransiska (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
This community service program was conducted in Ngegedhawe Village, Nagekeo Regency, East Nusa Tenggara, aiming to document and disseminate local history and cultural values that have traditionally been transmitted orally. Undocumented oral traditions face the risk of extinction due to decreasing engagement of young generations in traditional spaces, increasing social mobility, and the dominance of global digital culture. These conditions have led to a declining understanding among village youth regarding clan origins, social structures, and customary values. This program employed a Participatory Action Research (PAR) approach by actively involving traditional leaders and village youth throughout data collection, documentary film production, and dissemination processes. Methods included participatory observation, in-depth interviews, audio-visual documentation, and evaluation through pre-test and post-test of cultural understanding. The results indicate that documentary film functions effectively as a digital heritage medium, enhancing cultural literacy and strengthening local identity among younger generations. Beyond serving as a visual archive, the documentary also acts as an educational tool and fosters social cohesion within the community. Therefore, this program contributes significantly to sustainable local cultural preservation through participatory and adaptive audio-visual media.